The role of next generation sequencing in understanding male and female sexual development: clinical implications. Issue 5 (2nd September 2016) - Bashamboo, Anu; McElreavey, Ken
ABSTRACT: Introduction : Next Generation Sequencing is revolutionising our understanding of variation in the human genome and as costs reduce the sequencing of patient's genomes is become more routine. Areas covered : Here, we review the current challenges in the field and some of the efforts that are underway to resolve them. We describe how these technologies are impacting on our understanding of human sex development and the profound clinical implications of these technologies on conditions such as Disorders of Sex Development (DSD). Expert commentary : The sheer wealth of genomic data is generating new challenges—some are technical such as variant calling, or predicting the functional consequence of a variant—whereas others are more profound, such as establishing the link between extensive genomic information and the clinical presentation. Predicting disease phenotypes from genetic sequences is often extremely difficult because the genotype-phenotype relationship has proven to be far more complex than anticipated.